Ecological traps and boosters of ixodid ticks: The differing ecological roles of two sympatric introduced mammals - Doi, Kandai; Kono, Minori; Kato, Takuya; Hayama, Shin-ichi (Ticks and tick-borne diseases, 2021)
[Display omitted] The raccoon (Procyon lotor) and masked palm civet (Paguma larvata) are introduced species in Japan and have become abundant in human-inhabited environments. We surveyed tick infestations and tick ingestion by introduced raccoons and masked palm civets captured in Hayama, Kanagawa Prefecture, Japan between November 2018 and January 2020. We collected ticks from the body surface of animals and tick capitula from the gastrointestinal contents. We collected 18,357 ticks identified as Haemaphysalis flava, Haemaphysalis megaspinosa, Haemaphysalis longicornis, Ixodes ovatus, Ixodes tanuki, and Amblyomma testudinarium from 58 of 60 raccoons and 152 ticks, identified as H. flava and I. tanuki, from 16 of 41 masked palm civets. Furthermore, we obtained 16 capitula from 12 % of raccoons and 106 capitula from 63 % of masked palm civets. Raccoons harbored a greater number of ticks (all stages of H. flava and adult I. tanuki) compared with masked palmed civets, whereas the latter species ingested a greater number of nymphal and larval ticks. The results of this study extend our understanding of the ecological roles of two introduced wildlife species. The raccoon may act as an ecological booster, thereby increasing the success rate of bloodmeals and reproduction in ticks. In contrast, the masked palm civet may act as an ecological trap by effectively grooming to remove ticks and prevent bloodmeals.